Consequences in Georgia of a nationwide outbreak of Salmonella infections: what you don't know might hurt you. - Mahon, B E (1999)
OBJECTIVES: This study assessed the impact in Georgia of a nationwide salmonellosis outbreak caused by ice cream products and the effectiveness of the subsequent warning against eating the implicated products. METHODS: A telephone survey of 250 randomly selected Georgia customers of the ice cream producer was conducted 13 to 17 days after the warning. RESULTS: Respondents from 179 households representing 628 persons were interviewed. The median date of first hearing the warning was 5 days after it was issued, and 16 respondents (9%) had not heard it. Among those who had heard the warning, 42 (26%) did not initially believe the products were unsafe. In 22 (31%) of the 72 households that had the implicated ice cream when the respondent heard the warning, someone subsequently ate the ice cream. Diarrhea was reported in 26% (121/463) of persons who had eaten the products but in only 5% (8/152) who had not (odds ratio [controlling for household clustering] = 3.8; 95% confidence interval = 2.0, 7.5). We estimate this outbreak caused 11,000 cases of diarrhea in Georgia, 1760 (16%) with exposure after the warning. CONCLUSIONS: A large outbreak occurred in Georgia, much of which might have been prevented by a more timely and convincing warning.